MiR-27b inhibition contributes to cytotoxicity in patulin-exposed HEK293 cells. (30th April 2022) - Pillay, Yashodani; Nagiah, Savania; Tiloke, Charlette; Phulukdaree, Alisa; Chuturgoon, Anil A.
Abstract: Patulin (PAT) is a mycotoxin produced by Penicillium and other fungi that contaminate fruit. PAT targets the kidney and is associated with nephrotoxicity. Micro-RNAs (miRNA) may offer new insights into PAT-induced nephrotoxicity. Cytochrome P450 family 1, subfamily B, polypeptide 1 (CYP1B1), involved in metabolism of dietary toxins is negatively regulated by miR-27b and linked with the nuclear factor kappa B (NF-κB) pathway and peroxisome proliferator activated receptor gamma (PPARɣ) in renal fibrosis. This study investigated the effects of PAT on miR-27b, CYP1B1, PPARɣ and cytotoxicity in human kidney (HEK293) cells. HEK293 cells were exposed to PAT (2.5 μM, 24h). Protein expression of CYP1B1, PPARɣ, NF-κB (p65), pNF-κB (p65) (phospho-Ser563) and cleaved PARP-1 was quantified using western blotting. QPCR evaluated mRNA levels of CYP1B1, IL-6, miR-27b, OGG1, mtDNA, TFAM and UCP2 . Mitochondrial membrane potential and phosphatidylserine (PS) externalization was evaluated by flow cytometry while levels of ATP and caspase −9, −8, −3/7 activity was measured using luminometry. PAT significantly decreased miR-27b levels (p = 0.0014) and increased CYP1B1 mRNA (p = 0.0015) and protein (p = 0.0013) levels. PPARɣ protein expression was significantly increased (p = 0.0002) and associated with decreased NF-κB activation (p = 0.0273) and IL- 6 mRNA levels (p = 0.0265). Finally, PAT significantly compromised mitochondrial repair mechanisms and increased apoptotic biomarkers. PAT altered miR-27b levels and PPARɣ, with associated changes to NF-κB activation, downstream IL-6 and CYP1B1 expression. These results show that PAT impairs detoxification mechanisms leading to mitochondrial damage and apoptosis. In conclusion, PAT altered the epigenetic environment and impaired detoxification processes, supporting a mechanism for nephrotoxic outcomes. Graphical abstract: Image 1 Highlights: PAT, traditionally involved in oxidative stress, decreased miR-27b levels. A concomitant increase in CYP1B1 and PPARγ mRNA and protein levels were observed. Despite this, pathways related to inflammation and mitochondrial function were compromised. A significant increase in apoptotic biomarkers was noted. PAT altered the epigenetic environment and impaired detoxification processes.